Cognitive Impairment and Prevalence of Memory-Related Diagnoses among U.S. Older Adults - Yuting Qian; Xi Chen; Diwen Tang; Amy S. Kelley; Jing Li (Institute of Labor Economics (IZA), 2021)
Cognitive impairment creates significant challenges to health and well-being of the fast-growing aging population. Early recognition of cognitive impairment may confer important advantages, allowing for diagnosis and appropriate treatment, education, psychosocial support, and improved decision-making regarding life planning, health care, and financial matters. Yet the prevalence of memory-related diagnoses among older adults with early symptoms of cognitive impairment is unknown. Using 2000-2014 Health and Retirement Survey - Medicare linked data, we leveraged within-individual variation in a longitudinal cohort design to examine the relationship between incident cognitive impairment and receipt of diagnosis among American older adults. Receipt of a memory-related diagnosis was determined by ICD-9-CM codes. Incident cognitive impairment was assessed using the modified Telephone Interview of Cognitive Status (TICS). We found overall low prevalence of early memory-related diagnosis, or high rate of underdiagnosis, among older adults showing symptoms of cognitive impairment, especially among non-whites and socioeconomically disadvantaged subgroups. Our findings call for targeted interventions to improve the rate of early diagnosis, especially among vulnerable populations.
Keywords: I11; I14; J14; I18; R20; 330; cognitive impairment; cognitive aging; dementia; Medicare; memory-related diagnosis